Fat-to-heart crosstalk in health and disease - Lodewijks, Fleur; McKinsey, Timothy A.; Robinson, Emma L. (Frontiers in Genetics, 2023)
According to the latest World Health Organization statistics, cardiovascular disease (CVD) is one of the leading causes of death globally. Due to the rise in the prevalence of major risk factors, like diabetes mellitus and obesity, the burden of CVD is expected to worsen in the decades to come. Whilst obesity is a major and consistent risk factor for CVD, the underlying pathological molecular communication between peripheral fat depots and the heart remains poorly understood. Adipose tissue (AT) is a major endocrine organ in the human body, with composite cells producing and secreting hormones, cytokines and non-coding RNAs into the circulation to alter the phenotype of multiple organs, including the heart. Epicardial AT (EAT) is an AT deposit that is in direct contact with the myocardium and can therefore influence cardiac function through both mechanical and molecular means. Moreover, resident and recruited immune cells comprise an important adipose cell type, which can create a pro-inflammatory environment in the context of obesity, potentially contributing to systemic inflammation and cardiomyopathies. New mechanisms of fat-to–heart crosstalk, including those governed by non-coding RNAs and extracellular vesicles, are being investigated to deepen understanding of this highly common risk factor. In this review, molecular crosstalk between AT and the heart will be discussed, with a focus on endocrine and paracrine signaling, immune cells and inflammatory cytokines, as well as inter-organ communication through non-coding RNAs.